Multidisciplinary treatment for functional neurological symptoms: a prospective study - Demartini, Benedetta (J Neurol, 2014)
Although functional neurological symptoms are often very disabling there is limited information on outcome after treatment. Here we prospectively assessed the short- and long-term efficacy of an inpatient multidisciplinary programme for patients with FNS. We also sought to determine predictors of good outcome by assessing the responsiveness of different scales administered at admission, discharge and follow-up. Sixty-six consecutive patients were included. Assessments at admission, discharge and at 1 year follow-up (55 %) included: the Health of the Nation Outcome Scale, the Hospital Anxiety and Depression Scale, the Patient Health Questionnaire-15, the Revised Illness Perception Questionnaire, the Common Neurological Symptom Questionnaire, the Fear Questionnaire and the Canadian Occupational Performance Measure. At discharge and at 1 year follow-up patients were also asked to complete five-point self-rated scales of improvement. There were significant improvements in clinician-rated mental health and functional ability. In addition, patients reported that their levels of mood and anxiety had improved and that they were less bothered by somatic symptoms in general and neurological symptoms in particular. Two-thirds of patients rated their general health such as “better” or “much better” at discharge and this improvement was maintained over the following year. Change in HoNOS score was the only measure that successfully predicted patient-rated improvement. Our data suggest that a specialized multidisciplinary inpatient programme for FNS can provide long-lasting benefits in the majority of patients. Good outcome at discharge was exclusively predicted by improvement in the HoNOS which continued to improve over the 1 year following discharge.